Tithe, tax and zakat: a comparative analysis (2020)
Imposition of levy permeates religious and mundane affairs of people; and it takes a significant position not only in the religious affairs but also in the global economy. Many works have been done on tithe, tax and zakat without much attention on comparison. A comparison of them is necessary to weigh the relative impact of each on people. Therefore, the study compares them in the areas such as nature, objective and role. Using inductive qualitative methodology to explore some conceptual frameworks of Christian sources, sources of tax laws and Islamic sources, the paper finds that tithe, tax and zakat are viable means of eliminating poverty for individuals, organisations and economy. Tithe and zakat promise a just humane society for peace and prosperity in this world as an adjunct to salvation in the hereafter. The findings also show the trio are similar in the areas such as guarantee of fulfilment of basic needs, obligations, social, political and economic objectives but their differences lie in areas such as spiritual objective, reformation, heads of expenditure, chargeable items, rates and loss relief. The study reveals that non-Sharī‘ah compliant products such as liquor and pork which are not zakatable are fit for tithe and tax. The trio can ensure distribution of wealth for empowerment of the less privileged and for provision of infrastructural facilities. Zakat and tithe paid should be allowable deductions in the computation of tax with a view to relieving zakat and tithe payers of double taxation.